Invasive house geckos are more willing to use artificial lights than are native geckos. (14th July 2015) - Zozaya, Stephen M.; Alford, Ross A.; Schwarzkopf, Lin
Abstract: There is increasing concern about the ecological effects of light pollution, as artificial lighting spreads with urban expansion. While artificial lighting can negatively affect some species, others use it in novel ways. In tropical and subtropical regions, artificial lighting has created a novel niche: the 'night light' niche. Geckos living as human commensals (house geckos) are apparently well adapted to occupy this niche. In an urban area in north‐eastern Australia, we found that the invasive Asian house gecko H emidactylus frenatus (Gekkonidae) occupies a broader range of light environments in the field than does the native gecko G ehyra dubia (Gekkonidae). Experimental removal of the invasive species from a building indicated that it did not behaviourally influence the light environments chosen by the native species in the short term; they continued to use darker areas even after the invasive species was removed. In Y‐maze experiments, neither species showed a significant preference for light or dark areas; however, preliminary data suggest the invasive species was more willing to explore the Y‐maze than the native species. The willingness of H . frenatus to forage closer to lights, where insect abundance is typically higher, might account for its success as a global invader of human environments, even in areas where other gecko species are established.